2002
DOI: 10.1103/physrevb.66.073312
|View full text |Cite
|
Sign up to set email alerts
|

Spin separation in digital ferromagnetic heterostructures

Abstract: In a study of the ferromagnetic phase of a multilayer digital ferromagnetic semiconductor in the mean-field and effective-mass approximations, we find the exchange interaction to have the dominant energy scale of the problem, effectively controlling the spatial distribution of the carrier spins in the digital ferromagnetic heterostructures. In the ferromagnetic phase, the majority-spin and minority-spin carriers tend to be in different regions of the space ͑spin separation͒. Hence, the charge distribution of c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
3
9
0
Order By: Relevance
“…Hence, the exact many-spin wave functions of the Mn coupled to zerodimensional exciton feature ferromagnetic correlations, very much like bulk carrier mediated ferromagnetic order 23,25 and in agreement with experimental observations in photoexcited QD.…”
Section: Many-body Statessupporting
confidence: 65%
See 1 more Smart Citation
“…Hence, the exact many-spin wave functions of the Mn coupled to zerodimensional exciton feature ferromagnetic correlations, very much like bulk carrier mediated ferromagnetic order 23,25 and in agreement with experimental observations in photoexcited QD.…”
Section: Many-body Statessupporting
confidence: 65%
“…The Mn spins interact also with each other via short-range superexchange coupling. This Hamiltonian has been succesfully used to describe bulk, 15,23,24 two-dimensional, 25 and zero-dimensional QD. [18][19][20][21][22] In general, the Hamiltonian cannot be solved exactly and in most instances the mean field or some other approximations are used.…”
Section: A Hamiltonianmentioning
confidence: 99%
“…If the quantum well is made of a ferromagnetic DMS [13,14], resonant tunneling conditions should influence magnetic ordering as well. It has already been predicted that the critical temperature T c of the well can be strongly modified electrically [15][16][17]. Here we show that the magnetic ordering affects back the tunneling current, in a peculiar feedback process, leading to interesting dynamic transport phenomena.…”
supporting
confidence: 58%
“…Investigation based on mean field models reveal that p-d exchange interaction in δ-doped layers tends to be further enhanced by an additional confinement of the carriers, e.g., in a quantum well, leading accordingly to higher Curie temperatures (Fernández-Rossier and Sham, 2001;Kim and Yi, 2002;Lee et al, 2002). In such digital ferromagnetic heterostructures the occurrence of spin separation (the majority and minority-spin carriers reside in different spatial regions) has been predicted (Fernández-Rossier and Sham, 2002). Furthermore, it has been shown that the Curie temperature can be controlled over a broad range by external electric fields, which modulate the overlap of the subband wave functions with the Mn δ-doping profile (Nazmul et al, 2004;Lee et al, 2000), as schematically sketched in Fig.…”
Section: C4 Ferromagnetic Spin-rtdsmentioning
confidence: 99%